Perkembangan Peradaban Islam Pada Masa Kerajaan Islam di Indonesia: Kerajaan Mataram Islam dan Samudra Pasai - Adlyn Nazurah; Aulia Maharani Sulaiman; Bebi Annisa M. Siregar; Dina Rahmita; Muhammad Naufal Rahadi (Tabayyun : Journal Of Islamic Studies, 2024)
Indonesia is a country that has a history of Islamic Kingdoms, including the Islamic Mataram Kingdom and Samudra Pasai which were large kingdoms in the archipelago. Both have an important role in the spread of Islam and the development of culture in Indonesia. During the reign of the Islamic Mataram and Samudra Pasai Kingdoms, the development of Islamic civilization in the archipelago reached its peak through a rich cultural synthesis and broad intellectual relations. Islamic Mataram in Java became a center of cultural and religious exchange, combining Javanese traditions with deep Islamic values. Meanwhile, the Pasai Ocean at the northern tip of Sumatra emerged as a vital maritime trading base, facilitating intellectual dialogue and commerce across the Indian Ocean. This article was created in order to examine the two Islamic Kingdoms with the various aspects of civilization that they achieved during the period of the two Kingdoms in power.